Experimental Design and the Retention of Oil on Arctic Test Beaches - Owens, Edward H.; Robson, Wishart (ARCTIC, 1987)
Oil was laid down in a series of experiments at Cape Hatt, Baffin Island, N.W.T., on pairs of control plots in the upper intertidal zone at four beach sites, each with a different wave exposure, and on backshore pairs of control plots at two sites. The control plots were established as a basis for comparison with a series of intertidal shoreline cleanup experiments. Sites with different wave-energy exposures were selected in order to provide a range of energy level environments and also a variety of intertidal sediment characteristics. The experimental design of this phase of the project attempted to reproduce conditions similar to those that would result from a large spill. At each location one plot was oiled with an aged Lagomedio crude oil and the other with an emulsion of water in aged crude oil. . Observations and analytical results indicate that after seven or eight days dispersion and edge effects became significant on the intertidal plots. Data from the intertidal plots, therefore, were considered to replicate patchy oil contamination and were not representative of large natural spill situations beyond one week after the oil was laid down.Key words: Arctic, shoreline experiments, oil spills, oil retention, maximum oil loading Mots clés: Arctique, expériences sur le littoral, marée noire, rétention de pétrole, charge maximum de pétrole